Numerical Analysis of Dynamic Responses of Rock Containing Parallel Cracks under Combined Dynamic and Static Loading - Zihan Zhou; Zhonghui Chen (Geofluids)
Open-pit slopes contain numerous nonpenetrating, intermittent joints which maintain stability under blasting operations. The tip dynamic response coefficient (DRC) of parallel cracks in a typical rock mass under combined dynamic and static loading conditions was calculated in this study based on the superposition principle. The dynamic response law of the intermittent joint in the slope under blasting was determined accordingly. The influence of many factors (the disturbance amplitude of dynamic load, the lateral confining pressure, the length of rock bridge, the length between cracks, the staggered distance between cracks, and the crack inclination angle) on the dynamic response was theoretically analyzed as well. The ABAQUS numerical assessments were conducted on simulation models with parallel cracks under combined dynamic and static loading conditions. The results show that a larger dynamic load amplitude and smaller crack inclination angle/confining pressure result in greater Type II dynamic strengthening effect on the crack tip. When the length of the rock bridge between cracks (s) is smaller than the half length of the crack (a), the dynamic strengthening effect at the crack tip weakens gradually with increase in s; whens/a≥1, the strengthening effect is almost unchanged. With the increase in the staggered distance between cracks (h), the dynamic strengthening effect of the crack tip weakens at first and then strengthens; the strengthening effect is weakest when h/a=0.4; the crack propagation under combined dynamic and static loading is the most sensitive to the lateral confining pressure (σ3) and is the least sensitive to the inclination angle of the cracks (α). Theoretical results are validated by comparison with numerical simulation results. Such information regarding the dynamic response law of the parallel cracks in rock masses under dynamic and static loading conditions is conducive to further research on the mesofailure mechanism of open-pit mine jointed rock slopes under blasting operations.